Gastrointestinal endoscopy: infection and disinfection. Issue 11 (November 1983) - O'Connor, H J; Axon, A T
Abstract : The past decade has seen the development of an array of complex flexible fibreoptic instruments for gastrointestinal (GI) endoscopy, and an increasing use of these for diagnostic and therapeutic purposes. It has been recognised more recently that the use of contaminated endoscopic equipment can lead to serious and occasionally fatal infections. Infection with a wide variety of micro-organisms has been reported following oesophago-gastroduodenoscopy (OGD) and endoscopic retrograde cholangio-pancreatography (ERCP).